2019
DOI: 10.1001/jama.2019.15702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caspofungin vs Fluconazole Prophylaxis on Invasive Fungal Disease Among Children and Young Adults With Acute Myeloid Leukemia

Abstract: IMPORTANCE Children, adolescents, and young adults with acute myeloid leukemia are at high risk of life-threatening invasive fungal disease with both yeasts and molds. OBJECTIVE To compare the efficacy of caspofungin vs fluconazole prophylaxis against proven or probable invasive fungal disease and invasive aspergillosis during neutropenia following acute myeloid leukemia chemotherapy. DESIGN, SETTING, AND PARTICIPANTS This multicenter, randomized, open-label, clinical trial enrolled patients aged 3 months to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 26 publications
1
69
0
Order By: Relevance
“…While recommendations and clinical trial data are available to guide antifungal prophylaxis (7,(10)(11)(12)(13)(14), there is no single approach as prophylaxis must be customized to the needs of a given patient as well as local fungal epidemiology and susceptibility. Current strategies to protect against these most commonly encountered pathogens generally enlist an azole (one with mould activity if there is risk of Aspergillus) and trimethoprim/sulfamethoxazole (SXT) for Pneumocystis jirovecii pneumonia (PCP) (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…While recommendations and clinical trial data are available to guide antifungal prophylaxis (7,(10)(11)(12)(13)(14), there is no single approach as prophylaxis must be customized to the needs of a given patient as well as local fungal epidemiology and susceptibility. Current strategies to protect against these most commonly encountered pathogens generally enlist an azole (one with mould activity if there is risk of Aspergillus) and trimethoprim/sulfamethoxazole (SXT) for Pneumocystis jirovecii pneumonia (PCP) (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The flowchart of study selection for this network meta-analysis is shown in eFigure 1 in the Supplement . In total, 69 trials with 14 789 patients were included, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…63,64 Severe and prolonged neutropenia increases the risk for bacterial and fungal infection in children with ALL and AML, and recent clinical trials evaluated antimicrobial prophylactic strategies in these settings. 65,66 In Primary CMV infection is usually acquired during childhood and adolescence, followed by lifelong latency. Clinically significant activation from latent stage can occur during immunosuppression, in particular during impairment of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%